RELASI KUASA DALAM NOVEL “MAJNUN” KARYA ANTON KURNIA : PERSPEKTIF MICHEL FOUCAULT - Kartila S, Ninis; Nensilianti, Nensilianti; Hajrah, Hajrah; Abidin, Aslan (Fakultas Bahasa dan Sastra Indoensia, 2025)
This research discusses the discourse on power relations contained in the novel Majnun by Anton Kurnia using Michel Foucault's perspective. The focus of the research is the form of power relations found in the novel Majnun. This type of research is descriptive qualitative research which aims to examine the discourse that describes the form of power relations in the novel Majnun. Data was collected through technical literature study. The results of this research provide an overview of the four forms of power relations contained in the Majnun novel, namely religious, cultural, institutional and body power relations. Forms of body power relations are classified into three, namely power relations over individual, social and sexual bodies.